PERAN PEMERINTAH KOTA SURABAYA DALAM PENGATURAN TRANSPORTASI PUBLIK KOTA SURABAYA: STUDI PERKOTAAN PROGRAM “SUROBOYO BUS” - M. Bayu Winaryo; Ucu Martanto (Universitas Airlangga, 2020)
The research focuses on the role of government institutions related to regulating public transportation in the city of Surabaya. Transportation is one sector which influences the economic growth of a city, the potential to be utilized as a commodity used in obtaining sources of power by some parties. Because in the practice of management, how a ruling regime is able to regulate, control and determine the direction of policy that will influence various efforts taken by the government to encourage economic growth from the region so as to be able to